Effect of unilateral adrenalectomy on the quality of life of patients with lateralized primary aldosteronism - Marilisa Citton (BMC Surgery, 2019)
Abstract Background Primary aldosteronism (PA) is associated with an increased prevalence of anxiety and depression. Subnormal quality of life (QoL) scores in PA patients may be improved after surgical treatment. The aim of the study was to assess the impact of surgery on health-related QoL and depression status of patients suffering from PA, comparing the results with a control group of patients undergoing surgery for non-secreting adrenal tumors. Methods Data on QoL and depression status were prospectively collected, from January 2014 to January 2017, before, early after surgery (at 1 month) and at late follow up (at least 6 months) in patients with unilateral PA and in a control group with non-secreting adrenal tumors submitted to unilateral laparoscopic adrenalectomy. QoL was assessed using the Short Form 36 (SF-36) Health Survey for Physical (PCS) and Mental Component (MCS); the depression status by a 20-item depression scale (DS) questionnaire. Results Twenty-six PA patients and 15 controls were recruited. Biochemical cure of the disease was achieved following surgery in all PA patients; hypertension was cured in 31% of cases and improved in the remaining 69% of cases. No morbidity occurred in both groups. There were no significant differences between PA patients and controls concerning demographics, preoperative PCS, MCS and DS values. In patients with PA, MCS values improved at early (42.72 ± 13.68 vs 51.56 ± 9.03, p = 0.0005) and late follow up (42.72 ± 13.68 vs 51.81 ± 7.04, p < 0.0001); also DS values improved at early (15.92 ± 11.98 vs 8.3 ± 8.8, p = 0.0002) and late follow up (15.92 ± 11.98 vs 4.57 ± 6.11, p < 0.0001). In PA patients PCS values significantly improved at late follow up (51.02 ± 8.04 vs 55.85 ± 5.1, p = 0.013). Also in controls an improvement of MCS and DS scores was found at early and late follow up compared to preoperative values, while no significant differences in PCS were found. Conclusions Both PA and non-secreting adrenal tumors affect health-related QoL, worsening MCS and DS scores. Adrenalectomy is effective in curing PA, and improving MCS and DS scores at early and late follow-up, in patients with PA and non-secreting adrenal tumors. In PA patient surgery also significantly improves PCS at late follow up.